ANALISIS PENGENDALIAN PIUTANG USAHA PADA PT. ASTRA MULTI FINANCE (SPEKTRA) SAMARINDA - Ilmayani, Nur Fitri; Lau, Elfreda Aplonia (RJABM (Research Journal of Accounting and Business Management), 2020)
This study aims to determine and analyze the control of trade receivables at PT. Astra Multi Finance (SPEKTRA) Samarinda, considering that the company is increasing its profits by selling loans. The sale of credit does not immediately generate cash receipts, but it raises accounts receivable. This trade receivable will be effective in increasing sales if carried out supervision or control, it is necessary to study the effectiveness of internal control over the trade receivable. The theory that underlies this research is management accounting specifically about receivables and control of receivables. The analytical tools used in this study are Receivable Turn Over, Average Collection Period, Arrears Ratio and Billing Ratio The results showed that: first, Receivable Turn Over every year has increased which means that control of receivables from year to year more effective. Second, the Average Collection Period from year to year is getting faster which shows that the billing department can collect receivables into cash faster. Third, the calculation of the Arrears Ratio has decreased which shows that the amount of outstanding arrears has decreased, this is good for the company because the amount of receivables is getting smaller. Fourth, the calculation results of the Billing Ratio have increased each year. Thus it was concluded that control of receivables at PT. Astra Multi Finance (SPEKTRA) Samarinda has been carried out effectively.